Social Inequality in Every Day Laughing Discourse of Modern Russia - N. N. Zarubina (Vestnik MGIMO-Universiteta)
This article deals with the everyday discourse of the social inequality. The author analyses the ways in which humor is used to interpritate the social inequalities and the emergence of new privileged strata.